2019
DOI: 10.1109/jphot.2019.2935752
|View full text |Cite
|
Sign up to set email alerts
|

Largely Tunable Terahertz Circular Polarization Splitters Based on Patterned Graphene Nanoantenna Arrays

Abstract: Dynamic manipulation of wavefront is vital for massive free-space optical applications. Here we propose a set of largely tunable circular polarization splitters leveraging graphene nanoantennas with high efficiency reaching 83% and wide frequency tunability range of 2 to 5 THz. By synergizing the electrically tunable surface plasmons of graphene with phase gradient metasurface, we numerically demonstrate two kinds of polarization splitters with complimentary graphene patterns to realize electrical tuning of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For example, it was recently reported that 2D materials help strain relaxation during heteroepitaxial growth because of their slippery nature . Moreover, electronic and optical thin films can be combined with various 2D materials to realize numerous hybrid metadevices to further expand functionality to enhance device performance. Furthermore, cost reduction of material production by substrate recycling will give a chance to utilize expensive materials in the commercial market. Thus, the success of further development in the layer transfer technology will bring a new world in the electronic era with new physics, new device architectures, and new electronic applications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was recently reported that 2D materials help strain relaxation during heteroepitaxial growth because of their slippery nature . Moreover, electronic and optical thin films can be combined with various 2D materials to realize numerous hybrid metadevices to further expand functionality to enhance device performance. Furthermore, cost reduction of material production by substrate recycling will give a chance to utilize expensive materials in the commercial market. Thus, the success of further development in the layer transfer technology will bring a new world in the electronic era with new physics, new device architectures, and new electronic applications.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, plasmon polaritons in graphene/ hexagonal boron-nitride (h-BN) heterostructures exhibited a long intrinsic propagation length exceeding 10 µm (about 50 plasmonic wavelengths) 515 . Graphene can also be patterned with subwavelength structures to facilitate various metawaveguide devices for beam steering 516,517 , non-reciprocal SPP propagation 518 and topological edge plasmon 519 . In addition, plasmonic meta-waveguides carrying strongly enhanced local fields offer us a good platform for tunable light-matter interactions (e.g., nonlinear and Raman effects) when integrated with two-dimensional materials such as MoS 2 and graphene 348,520 .…”
Section: On-chip Plasmonic Meta-devices In Deep-subwavelength Scalementioning
confidence: 99%
“…The metasurface structure can also enable enhanced light-2D material applications for spontaneous control over harmonic signal generation and beam control. 137,304 At the same time, the 2D materials can be also patterned into atomically thin metasurfaces for tunable planar optics, 305,306 light sources, 307,308 beam splitters, 309 and so on.…”
Section: Metasurfacesmentioning
confidence: 99%